EFFECTIVENESS OF THE MERDEKA TEACHING PLATFORM (PMM) AS A MEDIA FOR TEACHER PROFESSIONAL DEVELOPMENT IN DRIVE SCHOOLS - Mulyani, Yani; Maulana, Rizka Husnu; Badrudin, Badrudin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the effectiveness of the Merdeka Mengajar Platform (PMM) as a medium for developing teacher professionalism in Sekolah Penggerak. The study was conducted in several Sekolah Penggerak in the Sindangwangi District of Majalengka Regency, involving teachers and school principals as the main participants. A qualitative approach with a case study method was used to explore in-depth data related to the experiences, perceptions, and impact of PMM usage on teacher professional competence. The research findings indicate that PMM significantly contributes to supporting the development of pedagogical and managerial competencies of teachers, especially through its integrated continuous development features. However, its effectiveness is influenced by factors such as technology access, user motivation, and school institutional support. This research recommends strengthening PMM usage training and improving supporting infrastructure to optimize the benefits of this platform in supporting the Sekolah Penggerak program